DOMAIN .go.id AS A VITAL DIGITAL OBJECT: ANALYSIS OF THE ENHANCEMENT OF CRIMINAL SANCTIONS IN THE ITE LAW - Abdurrahman Abdurrahman (Yayasan Pendidikan Islam Almatani, 2025)
This study aims to analyze the position of the .go.id domain as a Vital Digital Object from a national legal perspective and examine the provisions of enhanced criminal sanctions for cybercrimes that attack the .go.id domain based on the Electronic Information and Transactions Law (UU ITE). The .go.id domain not only functions as the technical identity of government websites, but also has a strategic role in government administration, public services, and the realization of the country's digital sovereignty. This study uses a normative legal research method with a statute approach and a conceptual approach. The analysis was carried out on relevant laws and regulations, legal doctrines, and the concept of national vital objects and digital infrastructure protection in the Indonesian legal system. The results of the study indicate that as the country's dependence on digital systems increases, the concept of national vital objects has expanded to include non-physical assets in the form of electronic systems and strategic digital infrastructure. The .go.id domain can be qualified as a Vital Digital Object because of its direct relationship with the government administration sector and information and communication technology, as regulated in Presidential Regulation Number 82 of 2022 concerning the Protection of Vital Information Infrastructure. The provisions on increased criminal sanctions for cyber attacks on the .go.id domain in the ITE Law serve as a preventive and repressive legal instrument that strengthens the protection of government electronic systems while safeguarding the country's digital sovereignty.